MOTIF PENGGUNAAN PAY LATER PADA WANITA KARIR KOTA SURABAYA (Universitas Negeri Surabaya, 2023)
Today, technology is developing rapidly and all of society's needs can be easily met. One of the most popular payment methods today, especially among career women, is Pay later. Therefore, it is interesting to examine the